FINANCIAL TARGET, STABILITY, AND FRAUDULENT FINANCIAL REPORTING: THE MEDIATING EFFECT OF FINANCIAL DISTRESS - Angelica Tri Nanda; Putri Wulanditya (Center for Indonesian Accounting Studies, 2025)
Research Objectives - This study examines the influence of financial targets and financial stability on financial statement fraud, as well as the role of financial distress in strengthening or weakening the relationship between financial pressure and fraudulent financial statement practices. Research Methods - This study uses a quantitative approach with secondary data in the form of financial reports from property and real estate companies listed on the Indonesia Stock Exchange, with a total of 180 observations obtained through purposive sampling. The data analysis technique uses panel data regression with E-Views 12 software. Research Findings - The results of this study indicate that financial targets and financial stability have a significant effect on financial statement fraud. However, financial distress is not proven to have a direct effect or mediate the relationship between financial targets and financial stability on financial statement fraud. This finding indicates that financial pressure and stability are more dominant influences on fraud than the company's financial distress. Theoretical and Policy Implications - The results of this study strengthen the fraud triangle theory, particularly regarding the dimensions of pressure originating from targets and the company's financial stability. Practically, these findings can provide a basis for management and regulators to strengthen oversight of financial target setting and maintain financial stability to minimize the risk of financial statement fraud. Research Novelty - Testing the role of financial distress as an intervening variable in the relationship between financial targets, financial stability, and financial statement fraud in the post-pandemic property and real estate sector.